2018
DOI: 10.4064/fm342-1-2017
|View full text |Cite
|
Sign up to set email alerts
|

Algebra, selections, and additive Ramsey theory

Abstract: Abstract. Hindman's celebrated Finite Sums Theorem, and its high-dimensional version due to Milliken and Taylor, are extended from covers of countable sets to covers of arbitrary topological spaces with Menger's classic covering property. The methods include, in addition to Hurewicz's game theoretic characterization of Menger's property, extensions of the classic idempotent theory in the Stone-Čech compactification of semigroups, and of the more recent theory of selection principles. This provides strong versi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…We have n∈N V n = ∅. By the result of Tsaban [35,Lemma 3.4., Theorem 2.7. ], the superfilter A contains an idempotent, large for the sequence V 1 , V 2 , .…”
Section: Richer Monochromatic Structuresmentioning
confidence: 88%
See 3 more Smart Citations
“…We have n∈N V n = ∅. By the result of Tsaban [35,Lemma 3.4., Theorem 2.7. ], the superfilter A contains an idempotent, large for the sequence V 1 , V 2 , .…”
Section: Richer Monochromatic Structuresmentioning
confidence: 88%
“…As we already mentioned in the introduction, Tsaban [35] considered theorems about colorings of natural numbers concerning colorings and covers of countable discrete spaces. This approach can be also applied to theorems considered here.…”
Section: Comments and Open Problemsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that the generalizations considered in this paper are of a quantitative nature, meaning that they deal only with cardinality, hence the results obtained do not preclude the possibility of obtaining other sorts of generalizations of Hindman's Theorem. For example, Tsaban [13] has shown that Hindman's Theorem may be viewed as a colouring theorem dealing with open covers of a certain countable topological space, and he proved a generalization of this theorem to arbitrary Menger spaces (which can have any arbitrary cardinality, although the objects coloured in this result are countable families of open sets). As another example, Zheng [14] has built on Todorčević's theory of Ramsey Spaces [12] to obtain results where finite subsets of ω together with real numbers are coloured, and monochromatic combinations of FU-sets and perfect subsets of R are obtained.…”
Section: Introductionmentioning
confidence: 99%